Production of blackberry cv tupy, depending on the intensity of pruning - Tullio, Leonardo; Ayub, Ricardo Antonio (Semina: Ciências Agrárias, 2013)
The blackberry crop is growing increasingly in Brazil, due to their nutritional qualities. Its management is essential for fruit quality, especially the production pruning. The objective of this study was to evaluate the effect of pruning intensity in the production of blackberry cv Tupy in the region of Ponta Grossa, PR. The entirely randomized experimental design consisted of six treatments with three repetitions, being the treatments: T1-2 rods, T2-3 rods, T3-4 rods, T4-5 rods, T5-6 rods and T6- 8 rods, a total of 18 parcels with 3 plants each. Were evaluated: plant production, fresh fruit, soluble solids, firmness and color. The number of stems left during pruning affects the productivity of blackberry cv. Tupy. For the parameters yield per plant and number of fruits per plant the ideal number of stems is 7,8. The number of stems per plant did not influence the fresh weight, soluble solids, firmness and color of the fruit. Considering productivity and ease of management is recommended to work with 6 stems per plant.